Pathology of Poverty Reduction of Imam Khomeini’s Relief Committee in Rural Areas (Case Study: Beneficiaries Covered in Tangestan City) - Samad Beheshti; Arman Hedari; Hassan Zahedi (پژوهش‌های راهبردی مسائل اجتماعی ایران, 2023)
Introduction ‎ In today's world, poverty continues to pose a significant challenge for numerous countries globally. Its adverse impact on various facets of society, including economic growth, social well-being, and human development, hinders endeavors toward sustainable progress, particularly in developing nations like Iran. Disturbing statistics reveal an unfortunate trend where not only is poverty steadily increasing overall in Iran, but it is also specifically on the rise within rural areas. Each passing year sees more people struggling to make ends meet and turning to charitable organizations for assistance. The establishment of the Imam Khomeini Relief Committee in February 1978 was a pivotal step toward addressing poverty and implementing measures to alleviate it. The organization's primary objective is to support deprived and needy individuals across Iran with the ultimate goal of eradicating poverty from the society. Assessing the effectiveness of this committee's policies is crucial for achieving its mission, especially considering its work in various rural areas throughout the country. Therefore, this research aimed to evaluate the success of these efforts thus far.‎